SYNTHESIS OF MATHEMATICAL MODEL FOR DIAGNOSTICS OF PNEUMATIC BRAKE SYSTEM OF ELECTRIC TRAIN - Mokin, Oleksandr; Mokin, Borys; Lobatiuk, Yuriy; Lobatiuk, Vitaliy (Scientific Works of Vinnytsia National Technical University, 2015)
Synthesis of mathematic model for diagnostics of pneumatic brake line of electric train has been performed, applying this model the location of line failure can be detected, without leaving the driver’s compartment. REFERENCES 1. Мокін Б. І. Математичні методи ідентифікації динамічних систем / Б. І. Мокін, В. Б. Мокін, О. Б. Мокін. – Вінниця: ВНТУ. – 2010. – 260 с. 2. Дмитриев В.Н. Основы пневмоавтоматики / В. Н. Дмитриев, В. Г. Градецкий. – М.: Машиностроение. – 1973. – 360 с. 3. Кошляков Н. С. Уравнения в частных производных математической физики / Н. С. Кошляков, Э. Б. Глинер, М. М. Смирнов. – М.: Высшая школа. – 1970. – 712 с. 4. Шкіль М. І. Вища математика. Книга 2 / М. І. Шкіль, Т. В. Колесник. – Київ: Либідь. – 2010. – 496 с. 5. Кошкин Н. И. Справочник по элементарной физике / Н. И. Кошкин, М. Г. Ширкевич. – М.: Наука. – 1972. – 256 с.